Tutors Agents for Teaching (2020)
The article begins by analyzing the studies carried out on tutors for teaching, carrying out a wide and exhaustive bibliographic search for related articles, all with the aim of obtaining a better knowledge of the applicability of the topic and through which it can be used in future applications. The research methods used were descriptive and exploratory, which were adjusted, managing to collect the necessary data. The research allowed demonstrating how the application of tutoring in education is presented as an agent for overcoming different problems evident in the learning processes. An effective application eliminates the inequalities of students in the academic context, which is an important contribution in search of improving the quality of education. The good results obtained in educational centers rethink the concept of learning in currently used methodologies, focusing on tutoring as a right of the student in her academic life. In the application there must be support from all the roles involved in learning (teachers and educational institutions), which guarantees success in its application.